Estudio de recepción de la hinchada de Centro Deportivo Olmedo, sobre los contenidos que consumen en las radios locales riobambeñas en el período enero – junio 2022. - Hidalgo Silva, Edwin Stalin (2023)
This study frames through the fan organizations that support Olmedo's club, organized bar teams, and the leaders, feeling the bustle of Olmedo daily in the soccer world. Using a mixed methodology to understand these agglomerates' interpretations was essential. It was vital to use some collection data tools like surveys and interviews. The reception that approximates an understanding of behavior and interpretation is constantly discussed on the Radio, relating to the entire environment of Olmedo club. It is perceptible to consider and analyze how people handle Radio. Suppose the information provided is liked or not by the fans who follow this historic Ecuadorian soccer team. The researcher felt a previous reception study to develop the current research to analyze the consumption of information that Club Olmedo fans have on the radios of Riobamba. The traditional media have been a channel for receiving information about this iconic team from the country's center, so it leaned explicitly on Olmedo de Riobamba club, starting from its fans, having its supporters in the organized bars. The fans are groups of people who have an affinity for a sports institution or simply fanaticism for something. The information around Olmedo is relevant and of social interest in the city due to the fans' demand for appropriate information. Consequently, it studies the clearly said perception that the fans have about the content they consume on the local radios of the city. Radio is a traditional means of communication, and has been present for several decades in events of social interest worldwide. It is a powerful tool for disseminating news of all kinds. Regarding sports, this traditional medium has been immersed in the most significant sporting events throughout history, such as World Cups, Olympic Games, soccer competitions, and others. However, it is a fact that over time, their way of communicating has changed, either due to the content, the demand for information, the fact that it did not reach the listener in a good way, or simply due to the arrival of new communication, that is, digital media. People began to migrate in the way in which they receive information, since, with the advent of digital media, they have preferred that ecosystem to get information, social networks are an obvious example. For this reason, the Radio has lost its space since people prefer new technologies because of their easy access or interaction.